Reconstructive Endovascular Treatment of Fusiform or Ultrawide-Neck Circumferential Aneurysms with Multiple Overlapping Enterprise Stents and Coiling - Jeon, P. (AJNR Am J Neuroradiol, 2012)
BACKGROUND AND PURPOSE: Fusiform aneurysms and ultrawide-neck circumferential aneurysms are still some of the most challenging lesions. The aim of this study was to investigate the efficacy and feasibility of the use of multiple overlapping Enterprise stents with coiling for the treatment of fusiform or ultrawide-neck circumferential aneurysms. MATERIALS AND METHODS: Twelve consecutive patients (9 men and 3 women; mean age, 56 years) with fusiform (n = 5) or ultrawide-neck circumferential (n = 7) aneurysms were treated with 2–3 overlapping Enterprise stents and coiling. The feasibility of this procedure and the clinical and angiographic outcomes of this technique were retrospectively evaluated. RESULTS: All patients were successfully treated by using this technique without any complications. Posttreatment angiographic results revealed grade 4 occlusion of the aneurysm in 6, grade 3 in 4, and grade 2 in 2 patients. Clinical follow-up was performed in all patients (mean, 16 months; range, 5–24 months). Nine patients had an mRS score of 0. Two had an mRS score of 1, one of whom had an initial mRS score of 2 due to the mass effect of a giant aneurysm; the other had a recurrent aneurysm presenting with SAH 5 years after clipping. Angiographic follow-up was performed in 10 patients at 6–20 months posttreatment. Nine had stable or improved occlusion, while 1 had a minor recurrence. CONCLUSIONS: In this small series, multiple overlapping Enterprise stents with coiling were a feasible and effective option for the treatment of fusiform and ultrawide-neck circumferential aneurysms. Further experience and follow-up are required to document the long-term efficacy of this treatment.